The Effect Of Valencene Biotransformation At Different Growth Phase Of Yarrowia Lipolytica - Nurdin, Zainur Fazira (Universiti Sains Malaysia, 2022)
Biotransformation is the process of transforming one organic compound from one form to another form for the purpose of reducing its persistence and toxicity by using microorganism such as yeast, fungi and bacteria etc. The biotransformation of valencene to nootkatone is getting higher demand in the industry due to their properties and characteristic as the flavor and fragrance especially in the food and flavor industries. As the demand for this nootkatone increase by years, many studies and research have been done to improve the quality and productivity of nootkatone synthesis. However, the chemical synthesis of nootkatone is threatening the environment as the process release heavy metal compound due to the hazardous chemical catalyst used. Thus, the biotransformation by using yeast catalyst is another alternative that can be considered to produce nootkatone. In this research, the effect of valencene biotransformation on exponential phase and stational phase was studied by using the biocatalyst Y. lipolytica. to produce nootkatone from the reaction. The growth curve shows the division of lag phase (0-6 hr), exponential phase (6-23 hr), stationary phase (23 -60 hr) and death phase (>60 hr). Biotransformation conducted in stationary phase is more favorable and higher conversion compared to exponential phase based on the concentration of valencene after biotransformation. The analysis of final sample in stationary phase shows lower valencene concentration due to higher conversion than in exponential phase